MON-377 Fracture Site in High-Energy Trauma Is Associated with Osteoporosis Risk - Chourpiliadis, Charilaos Paulos (J Endocr Soc, 2020)
Background: In our recent studies, we noted that patients with history of high energy fractures commonly have underlying endocrine abnormalities and low bone mineral density (BMD). In this expanded patient population, we aimed to investigate whether the fracture site can better predict the risk of abnormal BMD. Methods:We prospectively enrolled adult patients of both genders, with any history of high energy fracture. We measured serum PTH, vitamin-D and calcium and we performed BMD measurements with a DEXA scan. We split our subjects’ BMD, based on the lowest T- or Z-score in “Normal” (≥-0.9), “low bone mass” (LBM) (-1.0 to -2.4) and “Osteoporosis” (OST) (≤-2.5). We classified our patients according to fracture site, in vertebral, humeral, hip, tibial, malleolar-carpal, radial-ulnar and others, including rib fractures. Ratios were compared with χ (2) test, and continuous variables with one-way ANOVA. Results: We enrolled 444 consecutive subjects with 543 fractures. n=315 (71.0%) subjects had low BMD: OST 25.9% and LBM 45.1%. Among subjects <50 years of age, 43.1% had LBM and 9.2% OST, while in those >50, 46.3% had LBM and 36.6% OST (p<0.0001). The cohort’s mean lowest T/Z score was -1.6±1.2. Subjects with >1 fracture had more frequently low T/Z score (p=0.015). History of vertebral fractures provided the lowest mean T/Z score overall (-2.4±1.1), in females (-2.5±0.9) and subjects >50 (-2.5±1.1). The same holds true for hip fractures in males (-1.9±1.2) and subjects <50 (-2.1±1.4). Subjects with vertebral fractures had the lowest Hip (-1.7±1.2) and Spine (-2.3±1.2) T/Z scores, while those with tibial fractures had the lowest Radius T/Z score (-1.8±1.3). History of vertebral fractures was associated with the highest rate of OST (65.9%) in our overall population, males (50%), females (67.5%), subjects >50 (70.0%), while subjects with history of tibial fractures had the highest rate of normal BMD (46.2%), in males (80%) and females (50.4%), and those <50 (75.0%). Vitamin-D deficiency was present in 81.4% of all subjects. PTH was significantly higher in patients with OST compared to LBM or normal BMD (p=0.0006). Discussion: Patients with history of high energy fractures need to be screened with DEXA scan early, as they have high likelihood to suffer from osteoporosis.